2015
DOI: 10.2460/javma.247.8.932
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors associated with ovine progressive pneumonia in Wyoming sheep flocks

Abstract: Results indicated that OPP is prevalent in many Wyoming sheep flocks, which suggested that continued efforts are necessary to increase producer knowledge about the disease and investigate practices to minimize economic losses associated with OPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Despite strong evidence for a consistent association between TMEM154 genotype and susceptibility to MV infection in a wide range of conditions, several authors reported some animals serologically MV positive were carriers of protective genotype [19,22,25]. Several factors may influence the proportion of seropositive sheep with this genotype, such as heterogeneity of breeds, age, and sex of animals, management systems, viral strength, the dose of exposure, route of infection, and presence of different MVV strains or subtypes [19,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Despite strong evidence for a consistent association between TMEM154 genotype and susceptibility to MV infection in a wide range of conditions, several authors reported some animals serologically MV positive were carriers of protective genotype [19,22,25]. Several factors may influence the proportion of seropositive sheep with this genotype, such as heterogeneity of breeds, age, and sex of animals, management systems, viral strength, the dose of exposure, route of infection, and presence of different MVV strains or subtypes [19,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have also reported a lower prevalence [ 3 , 8 , 52 ]. In other continents, prevalence tends to be lower than in Europe [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings in this study were also much lower than in other countries of the world. For instance, a prevalence of 19% in Canada (Simard and Morley, 1991), 15.6% in culled ewes in Alberta, Canada (Fournier et al, 2006), 50% in Palestine (Hananeh and Barhoom, 2009), 28.8% in Germany (Hüttner et al, 2010), 15.3% was reported in Turkish sheep (Preziuso et al, 2010), 19.4% in Kirikkale district, Turkey (Azkur et al, 2011), 18% in Wyoming sheep, USA (Gerstner et al, 2015) and 29.6% in Khorasan-e Razawi province, Iran (Norouzi et al, 2015). Such inconsistency (variation) in the prevalence rates of MVV might be the variation in the diagnostic tests, sampling method used, the prevalence variability within the population studied, the characteristics of the animals forming the population, susceptibility of different breeds to the disease, management practices and measures taken to control the disease.…”
Section: Discussionmentioning
confidence: 99%